Diagnosis and treatment of hyperextension bicondylar tibial plateau fractures - Zhao, Ruibo; Lin, Zhangyuan; Long, Haitao; Zeng, Min; Cheng, Liang; Zhu, Yong (Journal of orthopaedic surgery and research, 2019)
To report the diagnosis, injury mechanisms, and imaging characteristics of hyperextension bicondylar tibial plateau fractures and examine the indications and feasibility of the modified anterior midline incision as a treatment strategy. We performed a retrospective analysis of 11 cases of hyperextension bicondylar tibial plateau fractures who were treated with open reduction and internal fixation, predominantly via an anterolateral and posteromedialdouble incision or a modified anterior midline incision. Radiological and functional evaluations were performed. Eleven patients were followed-up for a mean period of 11.5 months (range 3-24 months). The mean time to radiographic bony union was 12.5 weeks (range 10-26 weeks). At final follow-up, the average Rasmussen functional score was 26.8 (range 24 - 29); five patients had an excellent rating, and six a good rating. The average range of motion of the affected knees was 3.4-130° postoperatively. Fixation failure was not observed in any of the treated fractures. Hyperextension bicondylar tibial plateau fractures show a special Tiankeng-like collapse characteristic, while the changes in posterior tibial slope angle are easy to overlook. The modified anterior midline incision is a safe and effective approach for treatment of hyperextension bicondylar tibial plateau fractures with less rear displacement. Open reduction and double plating for the treatment of hyperextension bicondylar tibial plateau fractures provides excellent results.